PENGARUH MODEL PEMBELAJARAN DAN HASIL BELAJAR IPA TERHADAP KEMAMPUAN MEMECAHKAN MASALAH LINGKUNGAN HIDUP - Dede Margo (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2015)
The aim of the research is to identify the influence of learning model and IPA study result on the ability to solve problem in learning environmental education at the elementary school. This research was conducted in SD Laboratorium UPI Kampus Cibiru Bandung. Experimental method with factorial plan 2 x 2 is the method that was employed in this study. The sampling objects are 40- fourth grade students. Twenty of them achieved high result of environmental study and the remain were having low result. Two ways varian analysis (ANAVA) was used in hypothesis test continued by Tukey test. The research conclusion were: (1) Generally, students with the ability to solve environmental problem using constructivist model of learning are better than student using interactive model of learning.; (2) Students in high IPA study result, have the ability to solve environmental problem better after following the constructivist method of learning than using interactive method of learning; (3) Students in low IPA study result, both of constructivist and interactive method of learning did not give significance difference to the ability in solving environmental problem; (4) There are interaction between learning model and the IPA study result on the ability to solve environmental problem in the learning environmental education.